Obtention and characterization of coconut babassu derivatives (Scientia Agricola, 2015)
Babassu (Orbignya sp.) is a palm with extraordinary socioeconomic and ecologic importance found in humid tropical areas in Brazil, especially in frequently burned and degraded landscapes. There are several uses for babassu oil; however, its potential for providing other industrial products remains unexploited, due to the lack of scale and production structure. Oil and presscake extracted from kernels are industrially produced, while the remaining parts of the babassu coconut have the potential to add value as byproducts. This study aimed to establish conditions for the preparation of the raw material fruit of babassu for oil extraction by pressing and producing biodiesel by ethanolic transesterification. Babassu coconuts were dried at 75 and 90 °C. The separation of the fractions rich in fiber, starch, kernel and mesocarp was performed in appropriate equipments. The starch content in the mesocarp fractions of babassu coconuts dried at 75 and at 90 °C were 54 and 56 %, respectively and lipids represented 65 % of the kernel. Oil and press cake were obtained through hydraulic and continuous press, biodiesel was produced and the quality of products was compared. The total of saturated fatty acid in babassu oil was between 78 and 82 %, and the total of unsaturated fatty acids that promote good oxidative stability in the oil was in the range of 17 to 20 %. Oil obtained by cold pressing extraction and its biodiesel had better results in terms of quality. The quality of oils is within the Codex standard and biodiesel from oil extracted by cold pressing had higher oxidative stability.